The dynamic analysis of the applied force on javelin during final thrust by an elite javelin thrower - Gu, G. H.; Tsai, Y.-J.; Huang, C. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
According to the javelin rules, a throw is valid only if the tip strikes the ground before any other part of the javelin. So it is important to precisely control the applied force on javelin for further distance and tip-first landing. Two synchronized Redlake high-speed cameras (250 Hz) were used to videotape an elite thrower; a javelin with three fixed non-collinear markers was used in experiment. The aerodynamics and Newton-Euler equation were taken into account in the 3D inverse dynamic analysis. The results showed that the force was mainly on the axial direction as the whole hand gripped the javelin. However, as the portion of hand touching the javelin became lesser, the direction of force was changed from axial to lateral direction. The lateral torque was significantly larger than axial torque during the whole phase, and their maxima were 24.08 and 1.31 Nm, respectively. The results measured by this method were similar to those by force sensor, and it could be suitable for use in further researches.